Gestational diabetes and the neonate: challenges and solutions - Stewart A; Malhotra A (Dove Medical Press, 2015)
Alice Stewart,1 Atul Malhotra1,2 1Monash Newborn, Monash Health, 2Department of Paediatrics, Monash University, Melbourne, VIC, Australia Abstract: The prevalence of gestational diabetes mellitus (GDM) is rising worldwide, along with overweight and obesity. In utero exposure to hyperglycemia increases perinatal complications including preterm birth, macrosomia, neonatal respiratory distress, hypoglycemia, and polycythemia. More significantly, GDM places the offspring at risk of insulin resistance and type 2 diabetes mellitus, obesity and cardiovascular disease. The relative contributory roles of the intrauterine environment, shared genes, and postnatal environment on long-term outcomes are not yet fully understood. Maternal obesity in particular remains a significant confounding factor. Opportunities for ameliorating both the perinatal effects and long-term and intergenerational effects of GDM exist at the level of prevention of GDM, screening for and treatment of GDM, and postnatal interventions in offspring. Keywords: gestational diabetes mellitus, GDM, perinatal complications, long-term complications, hyperinsulinism, macrosomia